PENGARUH KOMPETENSI AUDITOR DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP PENDETEKSIAN FRAUD - Risma Choirunnisa (Jurnal Akuntansi Trisakti, 2022)
This research aims to examine the effect of auditor competence and the use of information technology on the detection of fraud in financial statements partially and simultaneously. The competency variable that must be carried out is because one of the requirements in the Auditing Standards that must be possessed by auditors, the use of information technology is a skill that must be possessed by auditors in this digitalization era, because the audit object is the result of information technology processing. The research population is 8 Public Accounting Firms in the Bandung City area and registered with the Financial Services Authority. This research used simple random sampling, with 41 questionnaires. The analytical method used is multiple linear regression. The results of the study indicate that auditor competence has an effect on fraud detection, the use of information technology has no effect on fraud detection.